First description of the female of Acantholycosa logunovi (Araneae: Lycosidae) - Fomichev, Alexander A.; Marusik, Yuri M. (Zootaxa, 2011)
With 26 named species (Platnick 2011), Acantholycosa Dahl, 1908 is a relatively large Holarctic genus in the wolf spider subfamily Pardosinae Simon, 1898. Acantholycosa was recently revised and 17 species were described as new to science (Marusik et al. 2004). The majority of species occur in Northern Asia and the highest species diversity is known from the Altai-Sayan Mountain System (18 species) (Marusik et al., 2004). Among the newly described species was Acantholycosa logunovi Marusik, Azarkina & Koponen, 2004 from Altai in Russia. The female epigyne of this species was found to be remarkably similar to those of A. norvegica (Thorell, 1872), while male palp was similar to those in A. plumalis species group. While collecting spiders in Altai the senior author collected over a dozen specimens belonging to Acantholycosa of which one pair was in copula. Study of this material revealed that males were conspecific with figures of the holotype of A. logunovi, but that females were different from those illustrated by Marusik et al. (2004). The females described as A. logunovi by Marusik et al. (2004) are instead A. norvegica and therefore females of A. logunovi remained undescribed up until now. Here we describe the female of A. logunovi, provide comparisons with related species and add to the known localities of this species.